Design, Fabrication and Evaluation of the Performance Characteristics of Hydraulic Ram by Varying the Various Parameters - Suseela P (Department of Land and Water Resources and Conservation Engineering, Kelappaji College of Agricultural Engineering and Technology, 1989)
In India, the agricultural production in many areas especially in hilly areas is very much affected by the non – availability of adequate power to lift water for irrigation. Main problems in enhancing irrigation facilities in hilly regions are their highly uneven topography and non availability of conventional sources of energy. The rapid depletion of conventional sources of energy and increasing demands have now focussed the attention on the need for developing a new economical and effective water lifting device which does not use the conventional sources of energy. A hydraulic ram may meet these requirements in hilly regions and can lift water without any external source of energy in the form of fuel or electricity. A hydraulic ram was designed and fabricated with cheap and commercially available materials. A constant supply head of 1.955 m was provided. Ram was designed for a maximum delivery head of 10 m. Provisions were given to vary the weight and stroke length of both the delivery valve and waste valve. A flange joint was incorporated valve and waste valve. A flange joint was incorporated between the delivery valve and air chamber to facilitate the quick opening and reinstallation of air chamber. Air chamber was fabricated with provisions to alter the volume, by changing the length of air chamber – the diameter of the air chamber was kept constant. The performance of hydraulic ram was evaluated mainly observing the delivery head – delivery discharge relationships. In each case the efficiency of the ram was evaluated. Typical performance characteristic curves were plotted for each of the changes in the conditions of operation. Effect of volume of air chamber on the performance of hydraulic ram was studied. The study revealed that the efficiency of the ram increases 1. as the weight of delivery valve increases 2. as the stroke length of delivery valve decreases 3. as the volume of air chamber increases 4. as the stroke length of waste valve decreases There is a steep reduction in delivery discharge with unit increase in delivery head. For a particular combination of waste valve, delivery valve and volume of air chamber, the maximum efficiency occurs at a moderate delivery head. For an increase in the stroke length of waste valve, there is a large reduction in best frequency. The beat frequency increases as the delivery head increases. The rate of decrease of best frequency with respect to the stroke length is higher for lower weights of was to valve. The ram stops functioning at certain low value of delivery head. This low valve of delivery head increases with increase in weight of delivery valve. Corresponding to a certain weight of delivery valve, there is a minimum weight of waste valve at which the ram functions satisfactorily. Further investigations are necessary to standardise different parts of the hydraulic rams for optimising their performance under varying conditions.